Bioenergy activated myocardial patch as well as preparation method and application thereof

By combining bioceramic nanoparticles and cardiomyocytes in a hydrogel matrix, bioenergy-activated myocardial patches were developed, which solved the problems of energy deficiency and metabolic disorders caused by myocardial infarction, and achieved the regeneration of myocardial tissue and The recovery of cardiac function has good biological activity and safety.

CN119258278APending Publication Date: 2025-01-07SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411369313.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Myocardial infarction leads to cardiomyocyte energy deficiency and metabolic disorders, leading to irreversible necrosis. The prior art is difficult to effectively promote myocardial tissue regeneration and cardiac function recovery.

Method used

Develop a bioenergic-activated myocardial patch that generates bioenergic activation signals by distributing bioceramic nanoparticles and cardiomyocytes in a hydrogel matrix, leveraging the release of inorganic active ions and physical morphology regulation, stimulating mitochondrial function, and promoting myocardial muscles Tissue regeneration and cardiac function recovery.

Benefits of technology

This myocardial patch effectively promotes myocardial injury repair, tissue regeneration and cardiac function recovery, has good biological activity and biosafety, and significantly improves the physiological function maturation of cardiomyocytes and ATP production ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258278A_ABST
    Figure CN119258278A_ABST
Patent Text Reader

Abstract

The invention relates to a bio-energy activated myocardial patch as well as a preparation method and application thereof. The biological energy activated myocardial patch comprises a hydrogel matrix, and biological ceramic nanoparticles and myocardial cells which are distributed in the hydrogel matrix. The biological energy activated myocardial patch provided by the invention can effectively promote repair of myocardial injury in vivo, regeneration of myocardial tissues and recovery of heart functions, and has good biological activity and biological safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomaterials, and in particular relates to a bioenergy activated myocardial patch and a preparation method and application thereof. Background Art

[0002] Myocardial infarction is caused by myocardial ischemia and hypoxia due to coronary artery obstruction, which in turn causes myocardial cell necrosis and irreversible damage to the vascular network. The heart requires a large amount of energy to maintain its regular contraction function. When myocardial infarction occurs, the supply of oxygen and nutrients is suddenly interrupted, resulting in a significant decrease in the production of adenosine triphosphate (ATP). Energy deficiency and metabolic disorders can lead to irreversible necrosis of myocardial tissue, causing catastrophic damage to cardiac function. Therefore, it is of great clinical significance to develop a myocardial patch that can be activated by bioenergy to promote myocardial tissue regeneration and restore cardiac function. Summary of the invention

[0003] In response to the above problems, the present invention provides a bioenergetic activated myocardial patch and a preparation method and application thereof. The bioenergetic activated myocardial patch stimulates mitochondrial function through the release of inorganic active ions and the regulation of physical morphology to produce a variety of bioenergetic activation signals, thereby promoting the regeneration of damaged myocardial tissue and the recovery of cardiac function.

[0004] In a first aspect, the present invention provides a bioenergy-activated myocardial patch, wherein the bioenergy-activated myocardial patch comprises a hydrogel matrix, and bioceramic nanoparticles and myocardial cells distributed in the hydrogel matrix.

[0005] Preferably, the hydrogel matrix is ​​at least one of methacrylated gelatin, gellan gum, gelatin, sodium alginate, and chitosan; preferably methacrylated gelatin (GelMA); the mass concentration of the hydrogel matrix is ​​4 to 10 wt%.

[0006] Preferably, the bioceramic nanoparticles are at least one of magnesium silicate, copper silicate, zinc silicate, calcium silicate, strontium silicate, and iron silicide; preferably magnesium silicate; the morphology of the bioceramic nanoparticles includes irregular shapes, nanospheres or nanotubes; preferably, the size of the irregular shapes is 10 to 1000 nm; the diameter of the nanospheres is 300 to 600 nm; the length of the nanotubes is 100 to 600 nm and the width is 5 to 20 nm.

[0007] Preferably, the content of the bioceramic nanoparticles is 0.01-10 wt % of the mass of the hydrogel matrix; preferably, the content of the bioceramic nanoparticles is 2-6 wt % of the mass of the hydrogel matrix.

[0008] Preferably, the content of myocardial cells in the bioenergy activated myocardial patch is 1 to 5×10 7 Pieces / mL.

[0009] In a second aspect, the present invention provides a method for preparing a bioenergy activated myocardial patch, comprising: (1) mixing bioceramic nanoparticles, a hydrogel matrix, a photoinitiator, and cardiomyocytes to obtain a bio-ink; (2) The obtained bio-ink is formed by 3D printing and cross-linked to obtain a myocardial patch activated by bioenergy.

[0010] Preferably, the photoinitiator is at least one of phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium, 2-isopropylthioxanthone, benzophenone, and methyl benzoylformate; preferably, phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium; more preferably, the content of the photoinitiator is 1 to 7 wt % of the mass of the hydrogel matrix.

[0011] Preferably, the parameters of the 3D printing molding include: setting the barrel temperature to 10-22°C, the deposition platform temperature to 2-10°C, the printing needle to 23-30G, the needle moving speed to 5-10mm / s, and the extrusion pressure to 10-100kPa.

[0012] Preferably, the cross-linking and curing time is 10 to 40 seconds.

[0013] In a third aspect, the present invention provides a use of the above-mentioned bioenergy activated myocardial patch in the preparation of tissue / organ repair materials.

[0014] Beneficial effects: The bioenergy activated myocardial patch of the present invention effectively promotes the repair of myocardial damage, the regeneration of myocardial tissue and the recovery of cardiac function in vivo, and has good biological activity and biosafety. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The basic properties of magnesium silicate (MS) nanoparticles with different morphologies; (a) is a scanning electron microscope (SEM) image of three magnesium silicate nanoparticles with different morphologies, namely irregular particles (IR), nanospheres (NS) and nanotubes (NT); (b) is a transmission electron microscope (TEM) image of three magnesium silicate nanoparticles with different morphologies and the distribution of magnesium (Mg), silicon (Si) and oxygen (O) elements; (c) is an X-ray diffraction (XRD) pattern of three magnesium silicate nanoparticles with different morphologies; Figure 2The basic properties and theoretical simulation calculations of biological inks and 3D printed patches containing magnesium silicate (MS) with different morphologies; (a) is the viscosity of biological inks containing MS nanoparticles with different morphologies in the temperature range of 10 to 37°C; (b) is the viscosity of biological inks containing MS nanoparticles with different morphologies in the temperature range of 0.1 to 100 s -1 Viscosity of bio-ink containing MS nanoparticles with different morphologies within the shear rate range; (c) Storage modulus (G') and loss modulus (G") of bio-ink containing MS nanoparticles with different morphologies at 16°C; (d) Patches 3D printed from bio-ink containing MS with different morphologies (all patches were stained with crystal violet); (e) Scanning electron microscope (SEM) image of 3D printed patches; (f) Magnesium ion release curve of 3D printed patches; (g) Silicon ion release curve of 3D printed patches; Interaction between GelMA molecular fragments and IR (h), NS (i) and NT (j) MS nanoparticles; (k) The theoretically calculated elastic modulus distribution of GelMA molecular fragments affected by MS with different morphologies; Figure 3 The changes of storage modulus (G') of 3D printed patches containing magnesium silicate (MS) with different morphologies during the culture process; Figure 4 Cell survival rate of 3D bioprinted myocardial patches containing different concentrations of NS in bio-ink; (a) is the live / dead staining image of myocardial patches after 1, 4, 7, 14, and 21 days of culture; (b) is the survival rate of rat cardiomyocytes (rCMs) in 3D bioprinted myocardial patches containing different concentrations of NS; Figure 5 Figure 3 shows the in vitro physiological functions of 3D bioprinted myocardial patches containing MS nanoparticles with different morphologies; (a) calcium transient images and Ca 2+ extracted from three different locations of myocardial patches containing 2% and 4% IR, NS, and NT. 2+ Flow signal atlas; (b) is the corresponding quantitative result of the number of peaks every 10 seconds based on the calcium transient signal; (c) is the corresponding quantitative result of the time required to reach the peak based on the calcium transient signal; (d) is the immunofluorescence staining image of the cardiac-specific protein connexin43 (CX-43) and α-actinin in the myocardial patch containing 2% and 4% IR, NS and NT; (e) is the semi-quantitative statistical result of CX-43 expression; (f)-(i) are the relative expressions of the cardiac-specific genes Tnnt2, Myh6 / Myh7, Gja1, and Cacna1a in 3D bioprinted myocardial patches; Figure 6Co-localization of MS nanoparticles with different morphologies and mitochondria of cardiomyocytes in 3D bioprinted myocardial patches; (a) is a transmission electron microscope (TEM) image of a myocardial patch, showing the distribution of MS nanoparticles with different morphologies in cells, where arrows indicate mitochondria and MS particles; (b) is a co-localization image of mitochondria and MS nanoparticles in a myocardial patch; Figure 7 The co-localization statistical results of MS nanoparticles with different morphologies and myocardial cell mitochondria in 3D bioprinted myocardial patches and the relative ATP production; wherein, (a) is the statistical result of the co-localization coefficient of mitochondria and MS nanoparticles in myocardial patches; (b) is the relative production of adenosine triphosphate (ATP) in 3D bioprinted myocardial patches containing MS nanoparticles with different morphologies; Figure 8 The repair effect of 3D bioprinted myocardial patches based on MS nanoparticles with different morphologies on myocardial infarction in rats; (a) is a representative photo of the heart and three cross-sections of the heart four weeks after surgery; (b) is a Masson trichrome staining section of the rat heart; (c) is the statistical result of the infarct area calculated based on the Masson trichrome staining image; (d) is the statistical result of the wall thickness of the infarct area calculated based on the Masson trichrome staining image; (e) is a representative echocardiogram of the rat heart 4 weeks after surgery; (f)-(i) are the quantitative results of ejection fraction (EF), shortening fraction (FS), left ventricular end-systolic internal diameter (LVIDs) and left ventricular end-diastolic internal diameter (LVIDd) calculated based on the echocardiographic results; (j) wheat germ agglutinin (WGA) immunofluorescence staining image of the infarct area of ​​the heart 4 weeks after surgery; (k) CX-43 and α-actinin immunofluorescence staining image of the infarct area of ​​the rat heart 4 weeks after surgery; Fig. 9The repair effect of 3D bioprinted myocardial patches based on MS nanoparticles with different morphologies on myocardial infarction in miniature pigs; (a) is a representative photo and electrocardiogram of the miniature pig heart before and after infarction; (b) is a representative photo of the miniature pig heart after myocardial patch transplantation; (c) is a representative photo of the electrical signal conduction test of the isolated heart 4 weeks after surgery, in which the arrow indicates the residual undegraded patch; (d) is a cross-sectional photo of the heart from the apex to the ligation site, in which the fibrotic area is circled with a dotted circle; (e) is a Masson trichrome staining of the miniature pig heart; (f) is the infarction calculated based on the cross-sectional photo of the heart. Statistical results of dead zone wall thickness; (g) is the statistical result of infarct area calculated based on cross-sectional photographs; (h) is a representative image of isolated heart electrical signal conduction; (i) is the statistical result of electrical signal conduction; (j) is the echocardiographic image of miniature pig heart 4 weeks after surgery; (k)-(n) are the ejection fraction (EF), shortening fraction (FS), left ventricular internal diameter at end diastole (LVIDd) and left ventricular internal diameter at end systole (LVIDs) calculated based on echocardiographic results; (o)-(r) are the statistical results of changes in EF, FS, LVIDd and LVIDs from 2 weeks to 4 weeks after surgery; Fig.10 The histological repair effect of 3D bioprinted myocardial patches based on MS nanoparticles with different morphologies on myocardial infarction in miniature pigs; (a) is the immunofluorescence staining image of CX-43 and α-actinin in the infarcted area of ​​miniature pig heart slices; (b) is the statistical result of the α-actinin area in the infarcted area of ​​heart slices; (c) is the statistical result of the CX-43 area in the infarcted area of ​​heart slices; (d) is the statistical result of the vascular density in the infarcted area; (e) is the immunofluorescence staining image of vascular markers vWF and α-SMA in the infarcted area of ​​heart slices; (f) is the immunofluorescence staining image of human nuclear antigen (HNA), which characterizes the integration of exogenous cells and host tissues in the patch; Fig.11 To evaluate the in vivo safety of 3D bioprinted myocardial patches based on MS nanoparticles with different morphologies implanted in miniature pigs; (a) is the hematoxylin-eosin (H&E) staining image of the liver, spleen, lung and kidney of the miniature pigs 4 weeks after surgery; (b) is the concentration of renal function-related indicators (serum creatinine (Cr), blood urea nitrogen (BUN)) and liver function-related indicators (serum aspartate aminotransferase (AST), alanine aminotransferase (ALT)) in the blood of the miniature pigs at 0, 2 and 4 weeks after surgery. DETAILED DESCRIPTION

[0016] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.

[0017] The present invention provides a bioenergetic activated myocardial patch, which comprises a hydrogel matrix, and bioceramic nanoparticles with bioenergetic activation activity (or as bioactive functional components) and functional myocardial cells distributed in the hydrogel matrix. The bioenergetic activated myocardial patch can stimulate myocardial cell bioenergetic activation and cell maturation by combining multiple physical and chemical signals.

[0018] In an optional embodiment, the hydrogel matrix is ​​at least one of methacrylated gelatin, gellan gum, gelatin, sodium alginate, and chitosan; preferably methacrylated gelatin (GelMA); the mass concentration of the hydrogel matrix is ​​4 to 10 wt%; preferably 6 wt%.

[0019] In an optional embodiment, the bioceramic nanoparticles are at least one of magnesium silicate, copper silicate, zinc silicate, calcium silicate, strontium silicate, and iron silicide, preferably magnesium silicate (MS). The magnesium silicate nanoparticles contain magnesium elements that can activate mitochondrial function and promote the production of adenosine triphosphate (ATP) and silicon elements that inhibit cardiomyocyte apoptosis. The magnesium and silicon ions released by the magnesium silicate nanoparticles can promote the mitochondrial function of cardiomyocytes and the maturation of the physiological functions of cardiomyocytes.

[0020] In an optional embodiment, the bioceramic nanoparticles are synthesized by a hydrothermal method. The morphology of the bioceramic nanoparticles includes irregular shapes (IR), nanospheres (NS) or nanotubes (NT); preferably, the size of the irregular shape is 10 to 1000 nm; the diameter of the nanosphere is 300 to 600 nm; the length of the nanotube is 100 to 600 nm and the width is 5 to 20 nm. In the patch described in the present invention, after the magnesium silicate nanoparticles are endocytosed by myocardial cells, they show different mitochondrial targeted enrichment effects, among which the enrichment of nanotubes is the most obvious, showing the strongest bioenergy activation and the highest ATP generation. In the myocardial patch, the magnesium silicate nanoparticles interact with the GelMA hydrogel matrix molecules, showing a microscopic elastic modulus higher than that of pure GelMA. Among them, the effect of nanotubes is the most obvious, followed by nanospheres, and the irregularity is weaker. This physical signal is conducive to the energy activation of myocardial cells.

[0021] In an optional embodiment, the content of the bioceramic nanoparticles is 0.01 to 10 wt % of the mass of the hydrogel matrix; preferably, the content of the bioceramic nanoparticles is 2 to 6 wt % of the mass of the hydrogel matrix; more preferably, the content of the bioceramic nanoparticles is 2% of the mass of the hydrogel matrix.

[0022] In an optional embodiment, the cardiomyocytes may be rat cardiomyocytes (rCMs) or human cardiomyocytes (hCMs) differentiated from human induced pluripotent stem cells. The content of cardiomyocytes in the bioenergetic activated myocardial patch is 1 to 5×10 7 / mL; preferably 3×10 7 If the concentration of cardiomyocytes is too low, the myocardial patch cannot show the overall beating function, resulting in discontinuous calcium transients, while if the concentration is too high, the proportion of cells in the overall patch is too large, resulting in a loose patch structure, which will be destroyed during the culture process.

[0023] The following is an exemplary description of the method for preparing the bioenergy activated myocardial patch provided by the present invention.

[0024] Preparation of bio-ink. In some embodiments, bioceramic nanoparticles, a hydrogel matrix, a photoinitiator, and cardiomyocytes are mixed and then rapidly cooled at 4°C to obtain the bio-ink.

[0025] In an optional embodiment, the photoinitiator is at least one of phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium, 2-isopropylthioxanthone, benzophenone, and methyl benzoylformate; preferably phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium; preferably, the content of the photoinitiator is 1 to 7 wt % of the mass of the hydrogel matrix.

[0026] The obtained bio-ink is 3D printed and cross-linked to obtain a myocardial patch activated by bioenergy. In some embodiments, after printing according to a set program, a blue light cross-linking instrument is used to perform photo-cross-linking to obtain the myocardial patch.

[0027] In an optional embodiment, the parameters of the 3D printing molding include: setting the barrel temperature to 10-22°C, the deposition platform temperature to 2-10°C, the printing needle to 23-30G, the needle movement speed to 5-10mm / s, and the extrusion pressure to 10-100kPa.

[0028] As an example, the method for preparing the bioenergetic activated myocardial patch includes: (1) Preparation of hydrogel matrix: Weigh 0.6 g of GelMA dry gel and 0.025 g of photoinitiator lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP), add 5 mL of phosphate buffer solution (PBS), heat in a water bath at 50-60°C for 30-90 minutes to dissolve, filter with a 0.22 μm bacteria filter membrane to sterilize, and place at 37°C for use; (2) Magnesium silicate nanoparticles (MS) with different morphologies were prepared by hydrothermal method. Three types of MS nanoparticles with different morphologies were synthesized by hydrothermal method under different conditions (the given mass and volume can be scaled up or down in the same proportion): Preparation of irregular morphology (IR) MS nanoparticles: 2.1 g Mg(NO3)2·6H2O was added to a solution of ethanol (60 mL) and deionized water (30 mL), and 2.3 g Na2SiO3·9H2O was dissolved in deionized water (10 mL). After stirring for 30-120 min, the Na2SiO3 solution was added to the Mg(NO3)2 solution and stirred for 5-60 min. Then, the liquid was added to a polytetrafluoroethylene-lined hydrothermal reactor (50 mL) and reacted at 150-220°C for 12-36 h. Next, the precipitate was collected and washed three times with deionized water and ethanol respectively. Finally, the IR particles were dried at 40-90°C for 12-48 h and stored at 2-10°C for use; Preparation of nanosphere (NS)-like MS nanoparticles: First, silica nanospheres were synthesized. 64 g of ethanol and 24 g of ammonia water were mixed and stirred at 20-40°C for 5-30 minutes. Then, tetraethyl orthosilicate (TEOS) (4.2 mL) was added to the liquid and stirred for 0.5-2 hours. Then, the liquid was centrifuged at 4000-12000 rpm for 5-30 minutes to obtain a white precipitate. After washing with deionized water and ethanol three times respectively, the SiO2 nanospheres were dried at 40-90°C and stored at 2-10°C for use. Then, NS was synthesized by the following method: 0.2 g of SiO2 nanospheres were added to deionized water (40 mL) and ultrasonically dispersed for 20-60 minutes. 0.3 g MgCl2·6H2O and 1.08 g NH4Cl were added to deionized water (60 mL), NH3·H2O (2 mL) was slowly added thereto and stirred for 20-60 minutes, and the mixed liquid was named liquid 1; SiO2 nanosphere dispersion and ethanol (100 mL) were quickly added to liquid 1 and stirred for 0.5-3 hours, then the liquid was added to a polytetrafluoroethylene-lined hydrothermal reactor (50 mL) and reacted at 120-200°C for 10-24 hours. Afterwards, the precipitate was collected and washed 3 times with deionized water and ethanol respectively. Finally, the NS particles were dried at 40-90°C and stored at 2-10°C for use; Preparation of nanotube (NT)-shaped MS nanoparticles: 0.28 g Na2SiO3·9H2O and 0.26 g Mg(NO3)2·6H2O were added to deionized water (2 mL) in two containers, respectively. Then, the Mg(NO3)2 solution and the Na2SiO3 solution were added to a mixed solution of ethanol (50 mL) and ethylene glycol (10 mL) and stirred for 5-90 minutes. Then, 1.00 g NaOH was added to the liquid and stirred for 0.5-3 hours. The liquid was added to a polytetrafluoroethylene-lined hydrothermal reactor (50 mL) and reacted at 150-220°C for 15-36 hours. Next, the precipitate was collected and washed 3 times with deionized water and ethanol, respectively. Finally, the NT particles were dried at 40-90°C and stored at 2-10°C for use. (3) Preparation of bioceramic particles: Taking the above-mentioned bioceramic nanoparticles of any morphology with an addition amount of 2% relative to the mass of the hydrogel matrix as an example, 0.012 g of MS was weighed, sterilized by ultraviolet irradiation for 2 h, added with 4 mL of PBS solution, and ultrasonically dispersed for 30-60 minutes and placed at 37°C for use; (4) Cell preparation: Taking rCMs as an example, the required rCMs were obtained by extracting Sprague-Dawley (SD) neonatal rat cardiomyocytes aged 1-72 hours. 3×10 8 Each rCMs was dispersed in 1 mL of PBS solution and placed at 37°C for use. Bio-ink preparation: 5 mL of GelMA, 4 mL of PB and 1 mL of rCMs were mixed to prepare bio-ink, and gelled in a refrigerator at 4 °C for 20 min; (5) Bioprinting: The barrel temperature was set to 16° C., the deposition platform temperature was set to 4° C., and printing was performed according to the set program. After deposition was completed, a blue light cross-linking instrument was used to cross-link to obtain the myocardial patch.

[0029] The present invention also provides in vitro culture conditions for the myocardial patch. In one embodiment, the printed myocardial patch is transferred to a 24-well culture plate, 1 mL of cell culture medium is added, the culture plate is covered, and the culture plate is placed in a cell incubator at 37°C and containing 5% CO2 for culture, and the culture medium is replaced every 48 hours.

[0030] In the present invention, the magnesium silicon ions released by bioceramic nanoparticles (such as magnesium silicate nanoparticles) as bioactive functional components promote the mitochondrial function of cardiomyocytes and the maturation of cardiomyocyte functions. Their morphologies (such as irregular shapes (IR), nanospheres (NS) or nanotubes (NT)) lead to different mitochondrial targeted enrichment levels and hydrogel matrix mechanical microenvironments, and the promotion of cardiomyocyte mitochondrial function is morphology-dependent. During the culture process, the three-dimensional reticular structure of the printed myocardial patch remains stable, the cell survival rate is high, and it has good biosafety.

[0031] The bioenergetic activated myocardial patch of the present invention promotes the maturation of myocardial cell physiological functions and the production of mitochondrial ATP in vitro. The maturation of myocardial cell physiological functions is due to the silicon ions released by magnesium silicate bioceramics; and the activation of mitochondria to increase ATP production is due to the magnesium ions released by magnesium silicate bioceramics on the one hand, and the morphology of magnesium silicate nanoparticles changes the mechanical microenvironment of the hydrogel matrix and the enrichment of MS nanoparticles in mitochondria after myocardial cells endocytose MS on the other hand. Specifically: Regarding the mechanical microenvironment, the microelastic modulus of NT after being incorporated into GelMA hydrogel increased most significantly, which was attributed to the structural alignment of the nanotubes, which helped NT to evenly distribute stress and effectively transfer loads, thereby increasing the microelastic modulus of the hydrogel-magnesium silicate composite. In contrast, the incorporation of NS resulted in a smaller increase in the microelastic modulus, because the spherical structure of NS resulted in a balanced stress distribution, and the interaction between NS and the GelMA molecular chain (such as entanglement, anchoring, etc.) was less than that of the slender nanotubes, so the increase in the microelastic modulus was smaller than that of NT. At the same time, IR had the lowest increase in the microelastic modulus due to its loose structure and weak interaction with the GelMA molecular chain. The increase in the microelastic modulus apparently resulted in the stiffness (G') of the myocardial patch showing NT-GelMA>NS-GelMA>IR-GelMA>GelMA, and the increase in stiffness was beneficial to the production of mitochondrial ATP. Regarding the influence of morphology on the enrichment of MS in mitochondria, relevant experiments have found that the three morphologies of MS are internalized to varying degrees, and are distributed around mitochondria or even enter mitochondria. This is attributed to the demand for magnesium ions in mitochondrial metabolism, which leads to the tendency of MS to enter mitochondria after internalization. Among them, the co-localization of NT and mitochondria is the most obvious. This is because NT has the smallest size and the highest aspect ratio, so its shorter end may be more likely to enter the interior of mitochondria to play a role. This shows that the morphology of MS nanoparticles (especially NT particles) affects their targeted enrichment in mitochondria, ultimately leading to the accumulation of Mg in mitochondria. 2+ The enrichment of mitochondrial ATP promotes the production of mitochondrial ATP to varying degrees. Therefore, the present invention promotes the maturation of the physiological function of cardiomyocytes in the patch and the production of mitochondrial ATP through the systematic design of the physicochemical stimulation signals.

[0032] The present invention provides the application of the above-mentioned myocardial patch in the field of myocardial infarction repair. Myocardial infarction models of SD rats and miniature pigs were established. After the myocardial patch was implanted on the surface of the infarcted myocardium, the repair function of the patch was verified by echocardiography, myocardial electrical conduction and histological staining of the myocardial slices in the infarcted area. The delivery of myocardial cells in the myocardial patch, the release of active ions and the activation of myocardial cell mitochondrial function by physicochemical signals effectively alleviate the imbalance of energy metabolism in the infarcted area, provide the infarcted area with restorative bioactive components and replacement active myocardial cells, and are beneficial to the regeneration of infarcted myocardial tissue and the recovery of cardiac function.

[0033] The present invention provides the biosafety of the myocardial patch in the field of repairing myocardial infarction in miniature pigs. In the myocardial infarction repair experiment in miniature pigs, the biosafety of the myocardial patch was comprehensively analyzed through electrocardiogram monitoring, body weight recording, blood biochemical index monitoring and tissue section staining of related organs (liver, spleen, lung, kidney).

[0034] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0035] Example 1

[0036] Preparation of magnesium silicate nanoparticles: Three kinds of MS nanoparticles with different morphologies (irregular magnesium silicate nanoparticles (IR), magnesium silicate nanospheres (NS) and magnesium silicate nanotubes (NT)) were successfully synthesized by hydrothermal method.

[0037] Figure 1 The basic characteristics of magnesium silicate (MS) nanoparticles with different morphologies; (a) is a scanning electron microscope (SEM) image of three magnesium silicate nanoparticles with different morphologies, namely irregular particles (IR), nanospheres (NS) and nanotubes (NT); (b) is a transmission electron microscope (TEM) image of three magnesium silicate nanoparticles with different morphologies and the distribution of magnesium (Mg), silicon (Si) and oxygen (O); (c) is an X-ray diffraction (XRD) pattern of three magnesium silicate nanoparticles with different morphologies. Scanning electron microscope (SEM) image ( Figure 1 a) shows that the size of IR ranges from tens of nanometers to hundreds of nanometers; the length of NT is 100 to 500 nanometers and the width is about 10 nanometers; the diameter of NS is about 500 nanometers. Further observation by transmission electron microscopy (TEM) revealed that both NS and NT have hollow structures ( Figure 1 b). Energy dispersive spectroscopy (EDS) confirmed the uniform distribution of Mg, Si and O elements inside the three nanoparticles. Figure 1 c X-ray diffraction (XRD) shows the phases of the three types of MS nanoparticles.

[0038] Example 2

[0039] Preparation of myocardial patch GelMA dry gel (12 wt%) and photoinitiator lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP) (0.5 wt%) were weighed and dissolved in phosphate buffer solution (PBS), heated in a 58 °C water bath for 1 h, and sterilized by filtration with a 0.22 μm filter membrane; MS was sterilized by ultraviolet light for 2 h in advance and then dissolved in PBS for ultrasonic dispersion for 30 min; then the cardiomyocyte dispersion, GelMA, and MS were mixed and blown evenly to form a bio-ink with uniform dispersion of each component, in which the cell concentration was 3×10 7 / mL, GelMA concentration was 6wt%, LAP concentration was 0.25wt%, MS was 0% (GelMA), 2% (2IR-GelMA, 2NS-GelMA, 2NT-GelMA), 4% (4IR-GelMA, 4NS-GelMA, 4NT-GelMA), 6% (6NS-GelMA) relative to the mass of GelMA. The bio-ink was added to a stainless steel ink cartridge equipped with a 27G needle (inner diameter 250μm) and cooled at 4℃ for 20 minutes; the extrusion pressure was adjusted between 20 and 60kPa, the barrel temperature was maintained at 16℃, and the deposition platform was cooled to 4℃; after printing was completed according to the set program, it was cross-linked for 20 seconds by a blue light cross-linking instrument. Finally, the myocardial patch was placed in a 24-well plate, 1mL of cell culture medium was added and cultured in an incubator (37℃, 5% CO2), and the liquid was replaced every 48h.

[0040] like Figure 2 From the rheological analysis shown in (ac), all bioinks exhibited excellent temperature sensitivity, shear thinning properties, and similar storage modulus (G') and loss modulus (G"), indicating that the bioinks are suitable for extrusion 3D printing. Figure 2 de are the optical photographs and SEM images of the printed representative myocardial patches, which have similar macrostructures and porous micronetwork structures. Figure 2 fg show the sustainable degradation of MS and the release of Mg and Si bioactive ions. Figure 2 hk, Figure 3 Combining experimental tests and theoretical simulation calculations, it is shown that the morphology of MS nanoparticles affects the microscopic elastic modulus G' after crosstalk between MS and GelMA molecules, ultimately leading to the addition of MS to increase the macroscopic storage modulus G' of the myocardial patch during the culture process, providing a favorable mechanical microenvironment for bioenergy activation.

[0041] Figure 4 ab are the results of cell live-death staining, which show that after adding MS, the cardiomyocytes in the patch survived well, and each group of patches had a cell survival rate of up to 90% within 21 days, indicating that MS has good cell safety.

[0042] Example 3

[0043] Physiological maturation of myocardial patches in vitro After 7 days of culture, the myocardial patches were subjected to calcium ion transient tests to characterize their beating physiological functions. The myocardial-specific proteins connexin43 (CX-43) and α-actinin of the myocardial patches were analyzed by immunofluorescence staining. At the same time, the expression of myocardial maturation-related genes Tnnt2, Myh6 / Myh7, Gja1, and Cacna1a were detected by reverse transcription-polymerase chain reaction (RT-PCR).

[0044] Figure 5 ac showed that the rhythmicity and frequency of calcium ion transients in the myocardial patch were improved after the addition of MS. Figure 5 de showed that at the protein level, the addition of MS promoted the expression of myocardial maturation-related protein CX-43. Figure 5 fi shows that at the gene level, the addition of MS promotes the expression of myocardial maturation-related genes Tnnt2, Myh6 / Myh7, Gja1, and Cacna1a. From the above results, the addition of MS nanoparticles significantly promotes the maturation of the physiological function of the patch. Specifically, the promotion effect when the addition amount is 2% is better than that when the addition amount is 4%; at the same time, the promotion effect of MS with different morphologies on synchronous contraction and myocardial maturity follows the rule that NT is the best, NS is the second, and IR is the worst. The above results show that the concentration and morphology of MS play an important role in regulating the maturity and physiological function of 3D bioprinted myocardial patches.

[0045] Example 4

[0046] In vitro bioenergetic activation of myocardial patches After 7 days of culture, the myocardial patch was fixed with 2.5% glutaraldehyde fixative for 1 hour, and the patch was treated with GelMA lysis solution for 2 hours to remove the GelMA matrix. The cells were collected by centrifugation and fixed in glutaraldehyde fixative, and TEM ultrathin sections were processed and TEM was used to observe the cellular endocytosis of MS nanoparticles with different morphologies in the patch. In order to further explore the intracellular fate of MS particles, fluorescein isothiocyanate (FITC) was grafted on the surface of MS nanoparticles. Specifically, taking 50 mg of MS grafting as an example, 0.4 g of sodium hydroxide and 4 mg of FITC were added to a solution of 0.5 ml of (3-aminopropyl) triethoxysilane (APTES) and 5 ml of ethanol, and the liquid was stirred in the dark for 24 hours; then, 50 mg of MS nanoparticles were added to the liquid and stirred for 12 hours; the mixture was centrifuged at 10,000 rpm for 15 minutes to obtain a precipitate, which was washed three times with deionized water and ethanol respectively, and the precipitate was dried to obtain FITC-labeled MS nanoparticles (MS-FITC). Subsequently, MS-FITC nanoparticles were added to the bio-ink, and 2IR-GelMA, 2NS-GelMA, and 2NT-GelMA myocardial patches were prepared. After 7 days of culture, the mitochondria in the patches were labeled and stained using a Mito-Tracker kit (C1034, Beyotime, China). Finally, images were acquired using a confocal laser scanning microscope (CLSM), and the Pearson correlation coefficient of the colocalization of mitochondria and MS nanoparticles was measured using Image J software.

[0047] Figure 6 a is a TEM image of the myocardial patch, indicating that the three types of MS nanoparticles can be internalized by rCMs, and the three types of MS nanoparticles are all located near the mitochondria that are closely related to cellular energy metabolism; among them, the localization relationship between NT and mitochondria is more obvious, and some NT enters the mitochondria. Figure 6 b is a fluorescent labeling image of MS nanoparticles and mitochondria, indicating that some IR and NT entered the mitochondria, while NS was mainly located around the mitochondria. Figure 7 a is the statistical situation of the co-localization coefficient between mitochondria and MS, indicating that NT is most obviously enriched in mitochondria. Figure 7 b is the relative adenosine triphosphate (ATP) production of the patch, indicating that the addition of MS activated the bioenergy metabolism of the patch and increased the ATP production. Among them, NT provided a more favorable mechanical microenvironment ( Figure 2 hk, Figure 3 ) and morphology-regulated mitochondrial enrichment, with the highest ATP production.

[0048] Example 5

[0049] Effect of myocardial patch on the repair of myocardial infarction in rats Myocardial infarction (MI) model was established using male SD rats weighing 225-250 g and randomly divided into 6 groups: sham group (Sham, n = 6), myocardial infarction group (MI, n = 6), GelMA group (n = 6), 2IR-GelMA group (n = 6), 2NS-GelMA group (n = 6) and 2NT-GelMA group (n = 6). Myocardial infarction model was induced by ligating the left anterior descending coronary artery (LAD), and all myocardial patches (diameter: 16 mm, height: 1 mm) were cultured for 7 days before implantation. For the sham group, rats only underwent thoracotomy, while rats in other groups underwent LAD ligation after thoracotomy; for the GelMA group, 2IR-GelMA group, 2NS-GelMA group and 2NT-GelMA group, the cardiac patches were implanted on the infarcted myocardium 15 minutes after ligation and fixed to the heart using fibrin glue. Echocardiography was monitored at 1 week and 4 weeks after surgery to characterize the changes in cardiac function in rats. Rats were killed 4 weeks after surgery, the hearts were collected, and the cross-sections of the hearts were recorded to observe the overall myocardial tissue infarction. Subsequently, the hearts were embedded in OCT embedding medium and frozen at -20°C for 48 hours, and the tissues were cut into 10μm thick slices using a freezing microtome. Subsequent sections were stained with Masson trichrome and immunofluorescence staining to evaluate the repair effect.

[0050] Figure 8 AD showed that the implantation of myocardial patch effectively reduced the infarct area and inhibited the thinning of ventricular wall thickness, among which 2NT-GelMA patch showed the best effect. Figure 8 ei is the changes in echocardiography and cardiac function-related indicators, indicating that the implantation of 2IR-GelMA, 2NS-GelMA and 2NT-GelMA patches significantly promoted the recovery of cardiac function, among which the promoting effect of 2NT-GelMA patch was the most obvious. Figure 8 j is wheat germ agglutinin (WGA) immunofluorescence staining of the infarcted area of ​​the heart section. It can be observed that both the MI group and the GelMA group had significant myocardial hypertrophy, while the implantation of the MS-containing patch inhibited the compensatory hypertrophy of the myocardium, and the cardiomyocyte size of the 2NT-GelMA group was the smallest. Figure 8k shows that compared with the MI and GelMA groups, the 2IR-GelMA, 2NS-GelMA, and 2NT-GelMA groups have more α-actinin-positive myocardium and more CX-43 expression, among which the 2NT-GelMA group shows the highest functional myocardial coverage. From the above results, it can be seen that the implantation of 3D bioprinted myocardial patches based on MS nanoparticles promotes myocardial repair after MI in rats. In addition, its in vivo repair effect is regulated by the MS morphology. The promotion effect follows the rule that NT is the best, NS is the second, and IR is the lowest, which is consistent with the results of Examples 3-4. In short, the morphology of MS nanoparticles simultaneously regulates the in vitro physiological function and in vivo repair effect of the 3D bioprinted heart patch, among which the 2NT-GelMA patch has the best biological activity and function.

[0051] Example 6

[0052] Effect of myocardial patch on the repair of myocardial infarction in miniature pigs Because the physiological structure and beating characteristics of the pig heart are very similar to those of the human heart, the myocardial infarction repair experiment in pigs is of great clinical significance. The present invention uses 12-month-old male miniature pigs weighing 25-30 kg to establish a myocardial infarction (MI) model, and randomly divides them into 4 groups: sham operation group (Sham, n = 3), myocardial infarction group (MI, n = 3), GelMA group (n = 3) and 2NT-GelMA group (n = 3). Miniature pigs are anesthetized with isoflurane (1-3%) and propofol (10mL / h), and then undergo thoracotomy. The MI model is induced by ligating the LAD for 10 minutes with a 5-0 polypropylene suture, and reperfused twice before permanent ligation. The successful establishment of the MI model is verified by the cyanosis of ischemia on the myocardial surface and the elevation of the ST segment on the electrocardiogram. All myocardial patches (diameter: 30 mm, height: 1 mm, 3 implanted per heart) were cultured for 7 days before implantation, and the living cells were human cardiomyocytes (hCMs) differentiated from human induced pluripotent stem cells (hiPSCs). For the sham group, the minipigs only underwent thoracotomy. For the GelMA group and the 2NT-GelMA group, the myocardial patches were fixed to the surface of the infarcted myocardium by using fibrin glue. Echocardiography was monitored before surgery and 2 and 4 weeks after surgery to characterize the changes in cardiac function in the minipigs. The minipigs were killed 4 weeks after surgery, and the hearts were quickly collected and immersed in KH solution. The electrical signal conduction of the isolated heart was characterized by a signal acquisition system (BL-420, TechMan, China). The stimulation electrode was connected to the end of the infarct area, and a dual-lead electrocardiogram (ECG) electrode was used for signal detection, and the output pulse was set to 2Hz. The heart was subsequently frozen and sectioned, and the repair effect was evaluated by Masson trichrome staining and immunofluorescence staining.

[0053] Fig. 9 a shows the cyanotic infarct area caused by myocardial infarction and the ST segment elevation of the electrocardiogram, confirming the construction of the acute myocardial infarction model. Fig. 9 b shows that the 3D bioprinted myocardial patch is firmly attached to the heart and completely covers the infarct area. Fig. 9 c shows that a small amount of residual undegraded patch can be seen on the heart surface 4 weeks after surgery, indicating stable adhesion of the myocardial patch throughout the repair process. Fig. 9 dg shows that the 2NT-GelMA group had the most similar tissue morphology to the sham operation group, with the thickest ventricular wall and the smallest infarct area. Fig. 9 hi showed that the myocardium of the 2NT-GelMA group had the best electrical conductivity, indicating that the electrical activity closely related to the recovery of cardiac function was significantly enhanced. Fig. 9 jr showed that the 2NT-GelMA patch enhanced the contractile activity of the anterior wall of the left ventricle in the infarcted heart. In the MI group, the shortening fraction (FS) and ejection fraction (EF) of the left ventricle continued to decrease 4 weeks after surgery, and the left ventricular systolic inner diameter (LVIDs) and left ventricular diastolic inner diameter (LVIDd) continued to expand. After the implantation of the 3D bioprinted myocardial patch, the FS and EF values ​​were significantly promoted from 2 weeks to 4 weeks after surgery, and the expansion of LVIDs and LVIDd was inhibited. Among them, the 2NT-GelMA group showed the best repair effect.

[0054] Fig.10 ac showed that the two patch implantation groups showed higher α-actinin and CX-43 expression in the infarcted area compared with the MI group, among which the 2NT-GelMA group showed the largest α-actinin and CX-43 positive coverage area. Fig.10 de showed that more new blood vessels were formed in the 2NT-GelMA group, indicating that during the repair process, the 2NT-GelMA patch activated angiogenesis, which is important for oxygen and nutrient transport during cardiac recovery. Fig.10 f shows that after cardiac patch implantation, hCMs in the patch migrated to the infarcted area and integrated with the host myocardial tissue.

[0055] In conclusion, the NT-containing 3D bioprinted cardiac patch can effectively integrate with the myocardial tissue of miniature pigs and significantly promote the repair of myocardial tissue and recovery of cardiac function after MI.

[0056] Example 7

[0057] Biosafety of myocardial patch for repair of myocardial infarction in miniature pigs In Example 6, relevant blood biochemical indices, electrocardiograms, body weight and other information of miniature pigs were detected before surgery, 2 weeks and 4 weeks after surgery. At the same time, after the miniature pigs were killed, sections of their main organs (liver, spleen, lungs, kidneys) were stained with hematoxylin-eosin (H&E) to evaluate their biosafety.

[0058] Fig.11 a shows that there were no obvious pathological changes in the liver, spleen, lung, and kidney in the patch implantation group compared with the sham operation group. Fig.11 b shows that there was no significant difference in liver function and renal function between the patch implantation group and the sham operation group. These results indicate that implantation of 3D bioprinted cardiac patches shows good biosafety for vital organs.

[0059] In summary, the bioenergy-activated myocardial patch prepared by the present invention has a good effect on myocardial tissue repair and regeneration.

Claims

1. A bioenergetic activated myocardial patch, characterized in that: The bioenergy activated myocardial patch comprises a hydrogel matrix, and bioceramic nanoparticles and myocardial cells distributed in the hydrogel matrix.

2. The bioenergetic activated myocardial patch according to claim 1, characterized in that: The hydrogel matrix is ​​at least one of methacrylated gelatin, gellan gum, gelatin, sodium alginate, and chitosan; preferably methacrylated gelatin; and the mass concentration of the hydrogel matrix is ​​4-10wt%.

3. The bioenergetic activated myocardial patch according to claim 1 or 2, characterized in that: The bioceramic nanoparticles are at least one of magnesium silicate, copper silicate, zinc silicate, calcium silicate, strontium silicate, and iron silicide; preferably magnesium silicate; the morphology of the bioceramic nanoparticles includes irregular shapes, nanospheres or nanotubes; preferably, the size of the irregular shape is 10 to 1000 nm; the diameter of the nanosphere is 300 to 600 nm; the length of the nanotube is 100 to 600 nm, and the width is 5 to 20 nm.

4. The bioenergetically activated myocardial patch according to any one of claims 1 to 3, characterized in that: The content of the bioceramic nanoparticles is 0.01-10 wt % of the mass of the hydrogel matrix; preferably, the content of the bioceramic nanoparticles is 2-6 wt % of the mass of the hydrogel matrix.

5. The bioenergetically activated myocardial patch according to any one of claims 1 to 4, characterized in that: The content of myocardial cells in the bioenergy activated myocardial patch is 1 to 5×10 7 Pieces / mL.

6. A method for preparing a bioenergy activated myocardial patch according to any one of claims 1 to 5, characterized in that: include: (1) mixing bioceramic nanoparticles, a hydrogel matrix, a photoinitiator, and cardiomyocytes to obtain a bio-ink; (2) The obtained bio-ink is formed by 3D printing and cross-linked to obtain a myocardial patch activated by bioenergy.

7. The preparation method according to claim 6, characterized in that: The photoinitiator is at least one of phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium, 2-isopropylthioxanthone, benzophenone, and methyl benzoylformate; preferably phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium; more preferably, the content of the photoinitiator is 1 to 7 wt % of the mass of the hydrogel matrix.

8. The preparation method according to claim 6 or 7, characterized in that: The parameters of the 3D printing molding include: setting the barrel temperature to 10-22°C, the deposition platform temperature to 2-10°C, the printing needle to 23-30G, the needle moving speed to 5-10mm / s, and the extrusion pressure to 10-100kPa.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The time for the cross-linking and curing molding is 10 to 40 seconds.

10. Use of the bioenergy activated myocardial patch according to any one of claims 1 to 5 in the preparation of tissue / organ repair materials.